Is there a COVID-19 vaccination effect? A three-wave cross-sectional study. Issue 3 (1st February 2022) - Ram, Yael; Collins-Kreiner, Noga; Gozansky, Einav; Moscona, Gal; Okon-Singer, Hadas
ABSTRACT: This research examines the impact of COVID-19 mobility restrictions and vaccinations on people's behavioural intentions to travel and their actual travel patterns. The study was conducted in Israel using three-wave cross-sectional analysis: June 2020 ( n =129), November 2020 ( n =211) and April 2021 ( n =208). The findings reveal that the main factor supporting tourism is the desire to resume travel and not vaccination. The study also shows that domestic travel is not a substitute for international travel, at least in the case of Israel. Attitudes towards tourism are significant predictors of domestic and international travel intentions and of actual domestic travel. Nevertheless, the belief that tourism is a source of recovery is related only to intentions to travel internationally. Non-clinical depression symptoms are negatively correlated with domestic tourism. Variables previously considered relevant to resuming tourism, e.g. vaccination, economic stress and health risk factors, have little or no influence on future demand, while attitudes regarding tourism emerge as the most important factor.